Post-diagnostic multivitamin supplement use and colorectal cancer survival: a prospective cohort study - He, Ming-ming; Wang, Kai; Lo, Chun-Han; Zhang, Yiwen; Polychronidis, Georgios; Knudsen, Markus D.; Zhong, Rong; Ma, Yuan; Wu, Kana; Chan, Andrew T.; Giovannucci, Edward L.; Ogino, Shuji; et al. (Cancer, 2024)
Background: Use of multivitamin supplements has been associated with lower incidence of colorectal cancer (CRC). However, its influence on CRC survival remains unknown. Methods: Among 2424 patients with stage I-III CRC who provided detailed information about multivitamin supplements in the Nurses’ Health Study and Health Professionals Follow-up Study, the authors calculated multivariable hazard ratios (HRs) of multivitamin supplements for all-cause and CRC-specific mortality according to post-diagnostic use and dose of multivitamin supplements. Results: During a median follow-up of 11 years, the authors documented 1512 deaths, among which 343 were of CRC. Compared to non-users, post-diagnostic users of multivitamin supplements at a dose of 3-5 tablets/week had lower CRC-specific mortality (HR, 0.55; 95% confidence interval [CI], 0.36-0.83, p = .005), and post-diagnostic users at doses of 3-5 and 6-9 tablets/week had lower all-cause mortality (HR, 0.81; 95% CI, 0.67-0.99, p = .04; HR, 0.79; 95% CI, 0.70-0.88), p < .001). The dose-response analysis showed a curvilinear relationship for both CRC-specific (pnonlinearity < .001) and all-cause mortality (pnonlinearity = .004), with the maximum risk reduction observed at 3-5 tablets/week and no further reduction at higher doses. Compared to non-users in both pre- and post-diagnosis periods, new post-diagnostic users at dose of <10 tablets/week had a lower all-cause mortality (HR, 0.81; 95% CI, 0.71-0.94, p = .005), whereas new users at a dose of ≥10 tablets/week (HR, 1.58; 95% CI, 1.07-2.33) and discontinued users (HR, 1.35; 95% CI, 1.14-1.59) had a higher risk of mortality. Conclusions: Use of multivitamin supplements at a moderate dose after a diagnosis of nonmetastatic CRC is associated with lower CRC-specific and overall mortality, whereas a high dose (≥10 tablets/week) use is associated with higher CRC-specific mortality.